2015
DOI: 10.1038/bmt.2015.17
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of pretransplant serum ferritin on the outcome of allogeneic hematopoietic SCT: a prospective cohort study by the Kanto Study Group for Cell Therapy

Abstract: This prospective study aimed to investigate the influence of pretransplant serum ferritin levels on the outcomes of allogeneic hematopoietic SCT (HSCT). In total, 190 patients with acute leukemia or myelodysplastic syndrome were consecutively enrolled. The patients were divided into two groups: low-ferritin group (o 1000 ng/mL) and high-ferritin group (⩾1000 ng/mL). The primary end point was the cumulative incidence of infection within 100 days after HSCT, which was similar between the two groups: bloodstream … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 25 publications
3
14
0
Order By: Relevance
“…Our results from this prospective study indicate that serum ferritin prior to alloSCT is associated to mortality after alloSCT. This trial served as confirmation of previous retrospective studies, which delivered preliminary results pointing in the same direction (7,(14)(15)(16)(17)(18). Of note, the Center for International Blood and Marrow Transplantation Research (CIBMTR) published an evaluation on different biomarkers and found that ferritin levels above 2500µg/ml were not associated with inferior alloSCT outcome (23) contrasting previously published studies (7,(14)(15)(16)(17)(18) and our results.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Our results from this prospective study indicate that serum ferritin prior to alloSCT is associated to mortality after alloSCT. This trial served as confirmation of previous retrospective studies, which delivered preliminary results pointing in the same direction (7,(14)(15)(16)(17)(18). Of note, the Center for International Blood and Marrow Transplantation Research (CIBMTR) published an evaluation on different biomarkers and found that ferritin levels above 2500µg/ml were not associated with inferior alloSCT outcome (23) contrasting previously published studies (7,(14)(15)(16)(17)(18) and our results.…”
Section: Discussionsupporting
confidence: 85%
“…In all these clinical situations serum ferritin, an acute phase and iron binding protein, has been demonstrated to be elevated (6)(7)(8)(9)(10)(11)(12)(13). Based on this background results, several retrospective studies and metaanalyses have suggested that serum ferritin may be of use as a biomarker during alloSCT (7,(14)(15)(16)(17)(18).…”
mentioning
confidence: 97%
“…Indeed, levels of ferritin, an iron storage protein used as an indicator of iron status and inflammation response, are increased in autoimmune diseases, infections, malignancy and other diseases [1012]. There is considerable evidence of the contribution of iron availability to mycobacterial growth in vitro as well as in experimental animal models [13,14], but reports on host iron status in response to anti-mycobacterial treatment are scarce. Among pulmonary TB (PTB) patients, high ferritin levels have been reported [1518], but few studies evaluated if ferritin levels reflect treatment outcomes [7,1921].…”
Section: Introductionmentioning
confidence: 99%
“…19,23 International Journal of Hematology and Oncology A higher threshold of pre-transplant serum ferritin levels may predict HSCT outcomes. 27 Pretransplantation serum ferritin may have significant prognostic value in patients with MDS undergoing myeloablative allogeneic HSCT, inducing a significant increase of non-relapse mortality. 5 Thus, iron status could be considered in transplantation decision-making in MDS.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21][22][23] Stem cell sources, distinct diseases and different protocols may also affect the impact of iron overload on the process of transplantation. [24][25][26][27][28] Unfortunately, some of the studies evaluating iron overload in transplant setting did not precisely show the patients with iron overload, mainly due to ignoring consideration of transferrin saturation along with hyperferritinemia for elimination of non-iron overload etiologies of hyperferritinemia (Table 1). Consequently, there are limited (and conflicting) data on the effect of adequatelydefined iron overload on prognosis of allogeneic HSCT.…”
Section: Introductionmentioning
confidence: 99%